Professionalism on teacher’s perception - Rosita Endang Kusmaryani; Juke R Siregar; Hanna Widjaja; Ratna Jatnika (Department of Psychology, Universitas Negeri Yogyakarta, 2018)
Regarding the phenomenon of teacher’s professionalism in Yogyakarta that is considered to be low, this study aims to explore the perceptions of teacher related to that matter. This research uses quantitative and qualitative approach with descriptive research type. Data were collected through open-questionnaires and interviews. The subject in this study consists of 74 teachers in Yogyakarta that includes public elementary school teachers, junior high school teachers and high school teachers. It is found that, based on teacher perceptions: (1) Professionalism includes expertise, social ability, self-integrity and productive behavior. (2) Teacher understands the term professional teacher better than teacher professionalism.